(untitled) (Research, Society and Development, 2022)
Objective: to analyze the scientific production on paternity from 2011 to 2021. Methodology: this is an integrative literature review with a qualitative approach, which sought articles published between 2011 and 2021, located through the descriptors: "Paternity" and " Parental care”. The electronic databases used were: Latin American and Caribbean Literature in Health Sciences (Lilacs), Scientific Electronic Library Online (Scielo) and Medical Literature Analysis and Retrieval System Online (Medline). Results: 13 articles were selected within the inclusions and exclusions items. Final Considerations: the active and affectionate participation of parents in the care services for the pregnancy-puerperal cycle is a fundamental element to promote improvement in health indicators related to aspects of life for children, adolescents, women and men. Therefore, it is necessary to expand and solidify actions in the different governmental instances so that they debate and emphasize the importance of paternity and care and the promotion of gender equality.